If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.66(x + 6) = 7 Reorder the terms: 0.66(6 + x) = 7 (6 * 0.66 + x * 0.66) = 7 (3.96 + 0.66x) = 7 Solving 3.96 + 0.66x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.96' to each side of the equation. 3.96 + -3.96 + 0.66x = 7 + -3.96 Combine like terms: 3.96 + -3.96 = 0.00 0.00 + 0.66x = 7 + -3.96 0.66x = 7 + -3.96 Combine like terms: 7 + -3.96 = 3.04 0.66x = 3.04 Divide each side by '0.66'. x = 4.606060606 Simplifying x = 4.606060606
| 375x+240x=15.000 | | x(x+3)=225 | | 3u^2-u-10=0 | | 5x-2+1= | | c+5/6=11/4 | | 4x(x-3)=40 | | 3x+7y=360 | | 7(t+2)+4t=2t-4 | | .25+2x=3 | | X-2/8-2x-3/12=x-4/7-11/4 | | 9u^5-3u^4-30u^3=0 | | .25+2x=1 | | x^3+2x^2-10x-10=0 | | 16=4(t+2) | | .25+2x=4.5 | | B-2/3=5/6 | | 11x+14=16x | | 6-[-3(2x-10+6)-5x]=22-4(4x-6) | | 20-26=9x-8x+2x-3 | | 2/7m=2 | | -28+47=-207x | | 23x-44=199 | | 0.10x+0.05(2-x)=0.10(7) | | 6(y+1)=-8y+6 | | 0.5-3=2c-24 | | 2x-15y=15 | | y=14x+13 | | 6(6v+6)-5+6v=1 | | 0=.5x^2-3x+1 | | 1=v-7+3 | | x+3=-(3x+3) | | 5/8k=5/8 |